Intranodal lymphangiography with Lipiodol® for the management of postoperative chylous ascites after abdominal aortic aneurysm surgery (Revista Argentina de Cirugía, 2026)
Chylous ascites is a rare complication after abdominal and/or pelvic surgery due to inadvertent injury to the lymphatic vessels during the procedure. We report the case of a 75-year-old female patient with an infrarenal abdominal aortic aneurysm with unfavourable vascular anatomy. For this reason, endovascular treatment was not indicated and she underwent aortobi-iliac prosthetic reconstruction requiring ligation of the left renal vein to place an infrarenal clamp. One week later, due to persistent fever and the presence of periprosthetic fluid collection on a computed tomography scan, an axillobifemoral bypass was performed and the aortic prosthesis was removed. On postoperative day 4, a milky output containing 394 mg/dL of triglycerides was discharged through the abdominal drains. A diagnosis of chylous ascites was made. As conservative management failed, intranodal lymphangiography with Lipiodol® was performed, which resulted in a progressive decrease in lymphatic output until it finally stopped after 14 days, avoiding additional surgical intervention.
Keywords: chylous ascites; postoperative lymphatic leakage; intranodal lymphangiography; Lipiodol